ASIMETRI INFORMASI DAN PENEKANAN ANGGARAN MEMODERASI PENGARUH PARTISIPASI ANGGARAN PADA SENJANGAN ANGGARAN - Saparudin Noor; Devi Permatasari; Osmad Mutaher; Muhammad Jafar Shadiq (CV. KAMPUS AKADEMIK PUBLISING, 2025)
This study aims to examine the effect of budget participation on Budgetary Slack, to examine the moderating effect of budget emphasis on budget participation and Budgetary Slack, to examine the moderating effect of information asymmetry on budget participation and Budgetary Slack. This type of research is quantitative. The population in this study is the Regional Development Planning Agency, Research and Development of West Kotawaringin Regency. The sample in this study was all employees involved in the budget preparation process at the Regional Development Planning Agency, Research and Development of West Kotawaringin Regency, totaling 39 respondents. The research data were collected using a questionnaire and analyzed using Moderated Regression Analysis (MRA). The results showed that budget participation had a positive and significant effect on budgetary slack. Budget participation and information asymmetry did not individually affect budgetary slack, and information asymmetry was not a moderating variable. Budget participation and information asymmetry individually affected budget emphasis, and budget emphasis was a moderating variable.